Development Of Learning Media In The Form Of Educational Monopoly In Islamic Religious Learning In Paud Kb Ar Rahima - Nuryana, Putri Fazila; Rahmariani, Nadifa (Educational Researcher Journal, 2025)
This research aims to develop learning media in the form of Educational Monopoly as a tool in learning Islamic Religion for early childhood in PAUD KB AR-Rahima. The research uses the Research and Development (R&D) method with a development model that includes the define, design, develop, and validate stages. This media is developed to be interesting, interactive, and in accordance with children's development, and contains memorization materials such as daily prayers, short surahs, and hadiths. The validation results of four experts—media, materials, language, and design—showed that the developed media was classified as very valid with an average score of 92.25%. This validation includes aspects of content correctness, visual appearance, ease of use, and language. This research supports previous findings that game-based media are effective in increasing children's interest and memory in religious learning. Therefore, Monopoly Education is suitable to be used as an alternative learning media that is able to foster children's motivation and Islamic character from an early age